Impact of racial discrimination in education and other adverse childhood experiences on black students’ mental health and wellbeing: an interpretative phenomenological analysis study - Nkasi Stoll; Sunehna Kayn; Heidi Lempp; Stephani Hatch (International Journal of Qualitative Studies on Health & Well-Being)
Introduction Black school students in the United Kingdom (UK) are exposed to racialized personal, institutional and systemic factors (e.g. racism and misogyny) that may impact their mental wellbeing and educational experiences. Minimal research exists to understand how racism and other adverse childhood experiences interact to shape students’ mental health and wellbeing as they progress through education before commencing university studies, which this study aimed to achieve. Methods Biographical Narrative Interpretive Method (BNIM) interviews (n = 15) were completed with Black UK university students who self-reported having struggled with mental health at school. Data were analysed using Interpretative Phenomenological Analysis (IPA). Results Three main themes were derived from Interpretative phenomenological analysis (IPA), pertaining to the students’ experiences of adverse childhood experiences, racism-related stressors in education, and coping strategies. Discussion The findings add value by offering recommendations for psychologists, educators, and policymakers to address racism and poor mental wellbeing in schools and to improve experiences and outcomes for Black students. Recommendations include self-reflection tools, funding for mental wellbeing interventions and resources, and enhancing professional courses to incorporate anti-racist curricula and practices.